2021
DOI: 10.1007/s11356-021-16171-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study on the relationship between particulate matter and microbial counts in hospital operating rooms

Abstract: Graphical abstract In this study, a systematic procedure for establishing the relationship between particulate matter (PM) and microbial counts in four operating rooms (ORs) was developed. The ORs are located in a private hospital on the western coast of Peninsular Malaysia. The objective of developing the systematic procedure is to ensure that the correlation between the PMs and microbial counts are valid. Each of the procedures is conducted based on the ISO, IEST, and NEBB standards. The procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 61 publications
0
10
1
Order By: Relevance
“…Those plates were pressed against the surface for 10 s without any lateral movement. The plates were taken to an incubator at 37°C for 2 days to read the CFUs, 22 and readings were taken after 48 h. 23 It occurred through the electronic and digital colony counter (Logen LS6000) allowing assistance in reading the CFUs. The literature shows several studies proposing the value of less than 2.5 CFU/cm to consider a clean surface.…”
Section: Methodsmentioning
confidence: 99%
“…Those plates were pressed against the surface for 10 s without any lateral movement. The plates were taken to an incubator at 37°C for 2 days to read the CFUs, 22 and readings were taken after 48 h. 23 It occurred through the electronic and digital colony counter (Logen LS6000) allowing assistance in reading the CFUs. The literature shows several studies proposing the value of less than 2.5 CFU/cm to consider a clean surface.…”
Section: Methodsmentioning
confidence: 99%
“…Extensive studies have also been made to associate the particle sizes with the microorganisms. A recent study conducted in an ISO Class 7 operating room reported that there is a positive correlation between microbes and particulate matter 5 (PM 5) and particulate matter 10 (PM 10) of 7% and 15%, respectively (Tan et al 2022c ). Figure 1 shows the onsite sampling of particulate matter, microbial and airflow volume and room pressure difference that was conducted in healthcare facilities.…”
Section: Current Assessment Of Airflow and Particle Concentration In ...mentioning
confidence: 99%
“…
Fig. 1 Onsite sampling of a particulate matter (Tan et al 2022c ), b microbial counts (Tan et al 2022c ), c airflow volume (Kamar et al 2020 ) and d room pressure difference (Kamar et al 2020 )
…”
Section: Current Assessment Of Airflow and Particle Concentration In ...mentioning
confidence: 99%
“…The third major concern of utilizing natural ventilation is that the thermal comfort and humidity conditions vary, depending on the outdoor air. Under such conditions, it has a high tendency of promoting the growth of microbes such as bacteria [17].…”
Section: Introductionmentioning
confidence: 99%